2019
DOI: 10.1111/jce.13942
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone pretreatment reduces the incidence of drug‐induced torsades de pointes in atrioventricular node‐ablated isolated perfused rabbit hearts

Abstract: Introduction: Higher progesterone concentrations are protective against druginduced prolongation of ventricular repolarization. We tested the hypothesis that pretreatment with progesterone reduces the incidence of drug-induced torsades de pointes (TdP).Methods and Results: Female New Zealand white rabbits (2.5-3.2 kg) underwent ovariectomy and were randomized to undergo implantation with subcutaneous 21-day sustained release pellets containing progesterone 50 mg (n = 22) or placebo (n = 23). After 20 days, hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
(51 reference statements)
0
6
0
1
Order By: Relevance
“…Progesterone and estrogens are reported to exert opposing effects on the heart. Progesterone pretreatment is shown to reduce the incidence of drug-induced TdP in atrioventricular node-ablated isolated perfused rabbit hearts ( Tisdale et al, 2019 ) and to protect against prolongation of action potential duration – APD (90) and triangulation associated with potassium channel inhibition ( Tisdale et al, 2011 ). In isolated guinea pig ventricular myocytes, progesterone shortened action potential duration, probably due to enhancement of the slow delayed rectifier K + current (I Ks ) under basal conditions and inhibition of L-type Ca 2+ currents (I CaL ) under cAMP-stimulated conditions ( Nakamura et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone and estrogens are reported to exert opposing effects on the heart. Progesterone pretreatment is shown to reduce the incidence of drug-induced TdP in atrioventricular node-ablated isolated perfused rabbit hearts ( Tisdale et al, 2019 ) and to protect against prolongation of action potential duration – APD (90) and triangulation associated with potassium channel inhibition ( Tisdale et al, 2011 ). In isolated guinea pig ventricular myocytes, progesterone shortened action potential duration, probably due to enhancement of the slow delayed rectifier K + current (I Ks ) under basal conditions and inhibition of L-type Ca 2+ currents (I CaL ) under cAMP-stimulated conditions ( Nakamura et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Older age is a risk factor, 2,3 which, in men, may be attributable to declining serum testosterone concentrations 4 . Testosterone and the androgenic female sex hormone progesterone have been shown in preclinical studies to protect against drug‐induced prolongation of ventricular repolarization 5,6 and arrhythmias 7,8 . In a randomized, double‐blind, placebo‐controlled crossover‐design proof‐of‐concept study, we found that transdermal testosterone attenuates drug‐induced QT lengthening in men ≥ 65 years of age 9 .…”
mentioning
confidence: 82%
“…4 Testosterone and the androgenic female sex hormone progesterone have been shown in preclinical studies to protect against drug-induced prolongation of ventricular repolarization 5,6 and arrhythmias. 7,8 In a randomized, double-blind, placebo-controlled crossover-design proof-of-concept study, we found that transdermal testosterone attenuates drug-induced QT lengthening in men ≥ 65 years of age. 9 The influence of oral progesterone on drug-induced QT lengthening was minimal.…”
Section: How Might This Change Clinical Pharma-cology or Translational Science?mentioning
confidence: 94%
“…In addition, Tisdale et al have recently shown in a randomized, double-blind, placebo-controlled crossover study that oral progesterone attenuated ibutilide’s effect on QTc prolongation [ 52 ]. In castrated rabbits implanted with sustained release pellets of progesterone or placebo, a significant decrease in the incidence of dofetilide-induced TdP (27% vs. 61%, respectively, p = 0.049), bigeminy (36% vs. 74%, p = 0.03) and trigeminy (18% vs. 57%, p = 0.01) [ 53 ] was demonstrated in the progesterone-exposed group. Overall, estrogens therefore play a role in lengthening QTc, while progesterone appears to be protective by limiting QTc prolongation.…”
Section: Role Of Estrogen and Progesterone During The Menstrual Cymentioning
confidence: 99%